Eating habits and other risk factors: are the future health care service providers really at risk for life style disorders! - Gandhi, Shreyash Jayantilal; Varia, Krunal Girishkumar; Dabhi, Mitesh; Choudary, Mahesh (International Journal of Research in Medical Sciences, 2017)
Background: Adolescence period is crucial position in the life, characterized by rapid rate of growth. It is a need to study risk factors among this group so applicability of primary prevention can be planned. It is essential to know that whether future care providers are having any risk of acquiring life style disorders as they will be the future role models of society. Objectives: To study the dietary and other risk factors for acquiring life style related disorders and to correlate various anthropometry measurements with these risk factors. Methods: A cross-sectional study. All medical, physiotherapy and nursing students from Government Medical College, Surat having met with age criteria of adolescent (17-19) as per WHO were included in the study. Pre tested structured self-administered questionnaire was used. It was having questions on various risk factors of acquiring life style related disorders and having anthropometry measurements to correlate. Data were entered and analyzed in MS excel. Results: Total 290 participants were enrolled, out of them 240 (82.76%) were females and 50 (17.24%) were males. Out of those, 153 (52.75%) were having a habit of eating outside the home at least once in a week. 80 (27.5%) participants reported that they never play outdoor games, 18 (6.21%) reported that they never do exercise. 21 (7.24%) were having BMI ≥25, From this total 21 participants, 17 (5.86%) were females and 4 (1.38%) were males. Out of total 240 females, 20 were having Waist Hip Ratio (WHR) >0.85, while no male is having WHR >1. Conclusion: Primary preventive measures for dietary change should be applied among future care providers. Life style change should also be advised to reduce the risk for life style disorders.